THE TEACHING OF ENGLISH FOR HOTEL AT NEPTUNE KEDIRI - Putra, Yulio Iswandaru (Jurnal Pendidikan Bahasa Inggris Proficiency, 2020)
This research was carried out to answer three objectives of study. Those are the teaching of English for Hotel at Neptune Kediri, response of the students towards the teaching of English for Hotel at Neptune Kediri and the tutor’s solution of the problems faced by students. The design was descriptive qualitative. The research instruments were observation sheet, interview note/sheet, document, and field note. The data collecting method were observation, interview, documentation, and field note. The result of this study showed that the teaching process of English for hotel at NEPTUNE had been supported by syllabus and lesson plan, the material was taken from book and internet, the media is using whiteboard and lcd tv. The method which was used was communicative learning and drill method, the technique which was applied in the class was direct question, problem based learning, discussion and role play technique. The evaluation of this program was taken by daily, mid semester and final semester. Tutor takes the student activeness and ability every meeting, mid and final evaluation take by interview test and witten test. From the result about the students’ perception was known that students had problems in constructing idea for speaking, less vocabulary and less confidence. From the students’ problem, the tutor gave solution by giving them tips and more discussion to increase their comprehension in speaking English.